Department of Technology Management and Economics - Gustafsson, Anton; Risberg, Josephine (My University, 2018)
the last decades, the margins in the automotive industry have decreased and a larger part of the profit comes from the aftermarket. At the same time, the customers require a higher service level in the aftermarket to always have their vehicles up and running, putting pressure on logistics to fulfil and exceed customer expectations. Therefore, it is more crucial than ever to have a good balance between a high service level and low costs. To find this appropriate level and maximise the company's performance, it is crucial to base the choice of transport provider on hard facts and not anyone's perception or feelings. The purpose of this master thesis is to investigate the cost of poor quality caused by transport providers, so it can be included in sourcing projects. To reach the aim of the thesis, interviews were carried out to identify the aspects that are part of poor quality for Volvo's transport providers, and further identify the actors and activities that are affected by poor quality. To identify how Volvo's dealers are affected, a survey was sent out to get generalisable numbers. The thesis has shown that it exists many aspects of poor quality for Volvo. But, due to constraints in measuring the size of the aspects and due to lack of performance measurements, only the cost of poor delivery precision can be added to the cost of poor quality at the time of writing. Still, including this cost of poor delivery precision can have a definite impact in the decision of transport provider. How large the impact is depends on the size of cost of poor quality relative the other factors in the Supplier selection model, which differ between sourcing projects.
Keywords: Samhällsbyggnadsteknik; Civil Engineering